Presence and depth of cold-water coral colonies on 3D reconstructions in the Lacaze-Duthiers canyon, CALADU_2019 ... - Fabri, Marie-Claire (SEANOE, 2019)
Coral assemblages were reconstructed in 3 dimensions (photogrammetry) using the 'Structure from motion' technique, at several locations in the canyon. The two colonial species, M. oculata and D. pertusum, were located on georeferenced photogrammetric models, with geographic coordinates and depths. • Spatial and vertical distribution of the two coral species Coral colonies were observed at different depths, D. pertusum between 339 and 254 m, M. oculata between 339 and 214 m. - PL 142-04: North cliff between 237 and 340 m, colonies of D. pertusum on boulders. Exploration then focused on coral colonies between 260 and 280 m, following the coral cover along a horizontal stratum. - PL144-06: On the eastern flank, on twin promontories, corals were aligned between 203 and 335 m along strata, mainly facing north. - Pl 143-05 and 145-07: On the western flank of the canyon, in very steep areas, dense colonies of D. pertusum were observed, with orange and white corals (Fig. 4). In general, D. pertusum was observed at ...